1984
DOI: 10.1037/0022-3514.47.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of analyzing reasons on attitude–behavior consistency.

Abstract: This article reports on three studies that investigated the effects of analyzing the reasons for one's feelings on subsequent attitudes and behavior. In the first two studies subjects were familiarized with attitude objects (puzzles or photographs), and half were instructed to analyze why they felt the way they did about these objects. Both self-report and behavioral measures of attitudes toward the objects were then assessed. In Study 3, subjects involved in dating relationships were or were not asked to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 27 publications
7
108
1
1
Order By: Relevance
“…The use of such information as well as extended deliberation may also reduce the weight of attitudes in decision making and weaken the consistency between attitudes and behavior. In three studies with different attitude objects, Wilson, Dunn, Bybee, Hyman, and Rotondo (1984) found that thinking about reasons reduced the correlation between attitudes participants indicated in questionnaires and measures of behavior or indirect measures of liking. For example, in their Study 2, people viewed different vacation scenes and were asked to indicate their liking of the pictures.…”
Section: Affective and Cognitive Focus In Consumer Judgmentsmentioning
confidence: 96%
See 1 more Smart Citation
“…The use of such information as well as extended deliberation may also reduce the weight of attitudes in decision making and weaken the consistency between attitudes and behavior. In three studies with different attitude objects, Wilson, Dunn, Bybee, Hyman, and Rotondo (1984) found that thinking about reasons reduced the correlation between attitudes participants indicated in questionnaires and measures of behavior or indirect measures of liking. For example, in their Study 2, people viewed different vacation scenes and were asked to indicate their liking of the pictures.…”
Section: Affective and Cognitive Focus In Consumer Judgmentsmentioning
confidence: 96%
“…They did not measure the individual differences in preferences for the alternatives. There are a few studies that manipulated the focus of participants and measured the attitude-behavior correlations (e.g., Wilson, et al, 1984). However, these studies used mostly self-reported SCARABIS, FLORACK, AND GOSEJOHANN Psychology & Marketing DOI: 10.1002/mar measures or, in one case, facial responses.…”
Section: H3mentioning
confidence: 97%
“…Other investigators have offered additional evidence of a tendency for cognitions to modify affective experiences. For example, recent evidence indicates that when people's behavioral predispositions toward some target person are based largely on affect (e.g., when they have just met a target), inducing them to think about that target can systematically alter their subsequent behavior toward him or her (e.g., Millar & Tesser, 1986;Wilson, Dunn, Bybee, Hyman, & Rotondo, 1984). Similarly, there is evidence that people "manage" their emotions by altering or juggling cognitions related to those emotions (e.g., Hochschild, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that the reasons generated during self-reflection mismatch one's actual reasons, predictions and choices based on the generated reasons will be disadvantageous or inaccurate. 94,98 There are situations, however, when self-reflection shows some benefit. Specifically, one paper has demonstrated that when self-reflection is about traits (not abilities, preferences or behaviors), is written down, and is explanatory rather than descriptive, it can result in slightly less-though still statistically significant-positive bias.…”
Section: A J P Ementioning
confidence: 99%
“…95 Similarly, Wilson and colleagues found than participants who reflected on their attitudes before reporting them showed lower attitude-behavior correspondence than participants who did not reflect. 98 Not only can self-reflection sometimes lead to sub-optimal choices, it can also hamper people's ability to predict their own behavior. This occurs because peoples' primary reasons for their preferences and behaviors are often either implicit or not easily verbalized.…”
Section: A J P Ementioning
confidence: 99%